Eficiência produtiva da carcinicultura nos estados do Ceará e Rio Grande do Norte - Norões, Alana Kedylla Monteiro (2017)
This dissertation consists of two articles, which are arranged in chapters. The first, entitled "Productive efficiency of shrimp farms in the state of Ceará", aims to investigate the degree and determinants of technical efficiency in shrimp production in the state of Ceará. Based on data from the 2011 Carcinculture Census, collected by the Brazilian Association of Shrimp Breeders (ABCC), 100 farms were characterized by a set of explanatory variables that describe the inputs used in the production and the way of managing the farms. To analyze the data, we estimated frontier models of stochastic production efficiency. The results showed that almost all farms (99%) can be considered technically inefficient. The factor that determined the inefficiency of the sample farms was the average storage density, since the other variables tested as inefficiency, which were: power of aerators per area, receipt of technical assistance and use of feed trays were not significant at a significance level of 5%, with this it is concluded that these do not generate inefficiency in the model. The second chapter, titled "Meta-frontier function of production and technical efficiency of shrimp farming in the states of Ceará and Rio Grande do Norte", aims to analyze the technological differences in shrimp production between the two largest national shrimp producers, Ceará and Rio Grande do Norte, operating in 2011 through the technological meta-frontier model. The results indicated that, when comparing the two states, Ceará has the highest average technical efficiency (ET) in relation to the meta-frontier.